The “FIFA 11+” injury prevention program improves body stability in child (10 year old) soccer players - Gatterer, Hannes; Lorenzi, Daniel; Ruedl, Gerhard; Burtscher, Martin (Biology of Sport, 2018)
The suitability of the FIFA 11+ prevention programme to improve selected performance outcomes in children aged < 14 years has not been established yet. This study aimed to investigate the effects of the FIFA 11+ programme on jump ability and stability in 10-year-old child soccer players. Sixteen young soccer players (aged 10 years) were randomly assigned to a conventional or a FIFA 11+ warm-up group. During a 5-week training period with 2 sessions per week the FIFA 11+ group warmed up with the 11+ programme, whereas the control group subjects performed their usual warm-up programme (e.g. running exercises with dribbling and/or passing techniques included). After the warm-up, both groups performed the same training exercises during each session. Before and after the training period, standing long jump performance and body stability (S3 Check, unstable uniaxial platform) were assessed. Significant improvements in the stability index were found in both groups (5.6±1.1 to 3.5±1.0 and 5.5±0.8 to 4.0±1.5 for the FIFA 11+ and the control group, respectively, p 0.05). Data indicate that in 10-year-old soccer players the FIFA 11+ programme may have the potential to improve stability. Thus, the FIFA 11+ programme might contribute to injury prevention and possibly to better soccer performance as well. This might especially apply if the programme is performed over a longer period and/or with more weekly training sessions. Based on the present results the inclusion of such a programme within the training practice of the child soccer player can be recommended.